Occurrence, speciation and transportation of heavy metals in 9 coastal rivers from watershed of Laizhou Bay, China. (April 2017) - Xu, Li; Wang, Tieyu; Wang, Jihua; Lu, Anxiang
Abstract: The occurrence, speciation and transport of heavy metals in 9 coastal rivers from watershed of Laizhou Bay were investigated. The largest dissolved concentrations of Cd, Cu and Zn in water were 6.26, 2755.00, 2076.00 μg/L, respectively, much higher than several drinking water guidelines. The greatest concentrations of Cu, Zn, Cr, Ni, Pb and Cd in sediments were 1462, 1602, 196, 67.2, 63.5 and 1.41 mg/kg, dw, respectively. Correlation and principal component analysis was also conducted to determine the extent between the concentrations of metals in water and sediment, as well as relevant parameters. Throughout the river stretch, most of Cr Zn, Cr, Ni and Pb bound to residual fraction, however, Cd was preferentially bound to the exchangeable phase. Among the 9 rivers, Yellow river account for 72.5%, 67.5%, 55.4%, 59.4%, 79.4% and 85.5% for Cr, Ni, Cu, Zn. Cd and Pb, respectively. The combined potential ecological risk indexes were used to evaluate potential risks. The majority of sampling sites from watershed of Laizhou Bay have moderate ecological risk from metals. The government should pay more attention to the ecological risk of river ecosystem which flow to Laizhou Bay. Highlights: High concentrations of Cd, Cu and Zn in sediment and water were found. Among the studied elements, Cd was most strongly present in the exchangeable phase. The total mass fluxes of six metals in 9 coastal rivers were 869 tons per year. The upstream of Jie River has very high ecological risk for the water body.